2021
DOI: 10.3389/fphar.2021.610164
|View full text |Cite
|
Sign up to set email alerts
|

The Punicalagin Metabolites Ellagic Acid and Urolithin A Exert Different Strengthening and Anti-Inflammatory Effects on Tight Junction-Mediated Intestinal Barrier Function In Vitro

Abstract: Scope: Ellagitannins are polyphenols found in numerous fruits, nuts and seeds. The elagitannin punicalagin and its bioactive metabolites ellagic acid and urolithins are discussed to comprise a high potential for therapeutically or preventive medical application such as in intestinal diseases. The present study characterizes effects of punicalagin, ellagic acid and urolithin A on intestinal barrier function in the absence or presence of the proinflammatory cytokine tumor necrosis factor-α (TNFα).Methods and Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The integrity of the intestinal epithelium, formed by a single layer of cells, is of primary importance to prevent and avoid the entrance of toxic and noxious agent into the mucosa and bloodstream. Recent research has demonstrated that the ellagic acid is particularly effective in strengthening the intestinal epithelium by reducing the expression of the claudin-4, -7, and -15 pore-forming proteins in Caco-2 cells [49], thus contributing to the epithelium integrity. Furthermore, in Caco2 cells, urolithin A reinforced the barrier function of the colonic epithelium by upregulation of the expression of proteins involved in the tight junctions through activation of the Nrf2-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the intestinal epithelium, formed by a single layer of cells, is of primary importance to prevent and avoid the entrance of toxic and noxious agent into the mucosa and bloodstream. Recent research has demonstrated that the ellagic acid is particularly effective in strengthening the intestinal epithelium by reducing the expression of the claudin-4, -7, and -15 pore-forming proteins in Caco-2 cells [49], thus contributing to the epithelium integrity. Furthermore, in Caco2 cells, urolithin A reinforced the barrier function of the colonic epithelium by upregulation of the expression of proteins involved in the tight junctions through activation of the Nrf2-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the highly beneficial effects of pomegranate in inflammatory diseases of colon (Lynn S Adams et al, 2006; R. Zhao et al, 2019) and also the high concentration of urolithins in colon typically achieved after consumption of ellagitannin‐rich food (Espín et al, 2013), some recent researches focused on anti‐inflammatory activity of urolithin A in animal models of colon inflammation (Hering et al, 2021; Larrosa et al, 2010).…”
Section: Pharmacological Activities Of Uroamentioning
confidence: 99%
“…Because of their abundance in the human diet and direct impact on human health, several studies have investigated the various biological activities of urolithins (especially UroA) which include cardiovascular protection (Gao, Huang, Tong, & Jiang, 2020), nephroprotection (Chen, Lei, Chen, & Zhou, 2020), neuroprotection (H. J. Lee et al, 2021), anti‐inflammatory activity (Hering, Luettig, Jebautzke, Schulzke, & Rosenthal, 2021), anticarcinogenic properties, antidiabetic activity (Yang et al, 2020), antiobesity (Xia et al, 2020), and antioxidant and antibacterial properties. Here, we comprehensively review the potential role of urolithins as a new therapeutic agent and investigate the molecular pathways for their biological effects that have been reported in cell culture, animals, and humans using various in vitro models and in vivo evidence.…”
Section: Introductionmentioning
confidence: 99%
“… 85 Nevertheless, punicalagin has poor pharmacokinetic parameters including 1) low bioavailability, 2) ineffective absorption, 3) high metabolism, and 4) high systemic elimination. 134 , 135 Therefore, designing a novel molecule for the treatment of CVDs such as punicalagin is advantageous.…”
Section: Challenges and Opportunities Of Nutritional Fruits-based Formulations And Drug Delivery Methods For The Treatment Of Cvdsmentioning
confidence: 99%